2019
DOI: 10.1016/j.clnu.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 6-month multi-strain probiotics supplementation in endotoxemic, inflammatory and cardiometabolic status of T2DM patients: A randomized, double-blind, placebo-controlled trial

Abstract: ClinicalTrials.gov Identifier: NCT01765517.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
138
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(145 citation statements)
references
References 37 publications
5
138
0
2
Order By: Relevance
“…High attrition rates are unfortunately common for clinical trials done in Saudi Arabia, especially for new interventions. In one study on the 6 month effects of probiotics among Saudi T2DM patients, 150 participants were randomized to receive either placebo or probiotics at baseline, but only 61 completed the trial, as the concept of ingesting live bacteria was relatively unheard of in the region, therefore affecting compliance [35]. In the present study, participants of the intervention were able to successfully apply the lifestyle changes for one year, but the majority declined to continue for 6 months more, citing changes in priorities and other personal reasons that would prevent them from fully engaging in the program.…”
Section: Discussionmentioning
confidence: 99%
“…High attrition rates are unfortunately common for clinical trials done in Saudi Arabia, especially for new interventions. In one study on the 6 month effects of probiotics among Saudi T2DM patients, 150 participants were randomized to receive either placebo or probiotics at baseline, but only 61 completed the trial, as the concept of ingesting live bacteria was relatively unheard of in the region, therefore affecting compliance [35]. In the present study, participants of the intervention were able to successfully apply the lifestyle changes for one year, but the majority declined to continue for 6 months more, citing changes in priorities and other personal reasons that would prevent them from fully engaging in the program.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Ecologic ® Barrier (Mixture of B. bifidum W23, B. lactis W52, L. acidophilus W37, L. brevis W63, L. casei W56, L. salivarius W24, Lactococcus lactis W19 and L. lactis W58) supplementation significantly reduced the blood endotoxin level and improved the lipid profile in diabetic patients. 33 Likely, the supplementation of the probiotic mixture (L. acidophilus T16, B. bifidum BIA-6, B. lactis BIA-6, and B. longum LAF-5) with or without prebiotics (maltodextrin) reduced the endotoxin level and improved inflammatory markers in hemodialysis patients. 34 The results of the current study supported that the supplementation of lyophilized L. paracasei HII01 amended the lipid profile in hypercholesterolemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ecologic ® Barrier supplementation also reduced the FBG, insulin, HOMA-IR values, and inflammatory cytokines level in T2D patients. The results suggested that multi-strain probiotic preparation could be an adjuvant therapeutic agent to improve diabetic and cardiovascular-associated metabolic parameters [38].…”
Section: Diabetes Patientsmentioning
confidence: 97%
“…Based on the randomized, placebo-controlled, double-blind studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] reviewed in the present article, the hypocholesterolemic effect of the probiotics was not significantly influenced by the diet. Studies reported based on the intervention of single-strain probiotic (E. faecium M-74 along with selenium [27]; Saccharomyces cerevisiae var.…”
Section: Opinion On the Hypocholesterolemic Effect Of Reviewed Probiomentioning
confidence: 99%
See 1 more Smart Citation